Decreased 8-oxoguanine DNA glycosylase 1 (hOGG1) expression and DNA oxidation damage induced by Cr (VI). (1st February 2019) - Xia, Hailing; Ying, Shibo; Feng, Lingfang; Wang, Haiming; Yao, Chunji; Li, Tao; Zhang, Yixiao; Fu, Sanjun; Ding, Donger; Guo, Xinnian; Tong, Yan; Wang, Xiaofeng; et al.
Abstract: Occupational exposure to Cr (VI) can cause DNA damage, genetic instability and elevate the risk of cancer. Here we investigated Cr (VI)-induced DNA damage and 8-oxoguanine DNA glycosylase 1 (hOGG1) gene expression in electroplating workers. The hOGG1 gene encodes a DNA repair enzyme that is crucial in DNA oxidation damage repair. Deficiency in hOGG1 DNA repair capacity contributes to the accumulation of DNA damage and genetic instability. To address the issues, we collected peripheral blood samples and urine samples from 162 electroplating workers and 84 control subjects. We measured blood chromium levels, urine chromium levels, DNA damage, and hOGG1 mRNA expression. We found significantly higher levels of blood chromium, urine chromium, and DNA damage in electroplating workers compared with controls, whereas mRNA levels of the hOGG1 gene were significantly lower in the exposed workers. Furthermore, in electroplating workers we found that blood Cr had a positive association with DNA damage as measured with the tail DNA%. Meanwhile, tail DNA% was positively associated with hOGG1 mRNA expression. Finally, the effect of potassium dichromate treatment was investigated in a human B lymphoblastoid cell line (LCL). We observed that potassium dichromate induced a concentration-dependent decrease in hOGG1 mRNA. After removing the K2 Cr2 O7 -containing medium for 3 days and 7 days, the abundance of hOGG1 mRNA expression recovered to a similar level as the controls. Collectively, our findings suggest that decreased hOGG1 mRNA expression in occupationally exposed populations partially contribute to Cr (VI) induced DNA damage. Graphical abstract: Highlights: Occupational exposure to Cr (VI) was associated with increased levels of DNA damage and decreased levels of hOGG1 expression. There was a positive correlation between blood Cr concentration and DNA damage in electroplating workers. Treatment of cells with Cr (VI) led to an initial down-regulation of the hOGG1 gene mRNA. Decreased hOGG1 mRNA expression in occupationally exposed populations partially contribute to Cr (VI) induced DNA damage.